SYNTHESIS OF NANOSILICA FROM TUKAD TELAGA WAJA SAND USING THE COPRECIPITATION METHOD WITH NaOH VARIATIONS - Ni Kadek Cinta Eka Putri Jayanti; Ida Bagus Putu Mardana; Putu Yasa; I Komang Restu Widi Artha (Universitas Mataram, 2026)
Volcanic sand is a potential natural silica source for the synthesis of high-value nanosilica materials. This study investigated the effect of NaOH concentration on the chemical composition, crystallinity, and morphology of nanosilica synthesized from Tukad Telaga Waja volcanic sand using the coprecipitation method. The utilization of Tukad Telaga Waja volcanic sand as a local precursor for nanosilica synthesis remains rarely reported, particularly regarding the influence of alkaline extraction conditions on nanosilica formation. The synthesis was carried out at 6 M, 7 M, and 8 M NaOH, followed by acid precipitation. The synthesized materials were characterized using X-ray fluorescence (XRF), X-ray diffraction (XRD), and Scanning Electron Microscopy (SEM). The XRF results showed that increasing NaOH concentration improved the SiO₂ purity of the synthesized nanosilica from 96.4 wt% at 6 M to 98.9 wt% at 8 M, indicating enhanced silica extraction during alkaline dissolution. XRD analysis confirmed that all samples exhibited an amorphous structure, with a broad diffraction hump centered at approximately 23 ° in the 2θ range of 20°–30 °. SEM observations revealed irregular granular morphology with agglomerated particle structures. Image analysis of the SEM micrographs using a log-normal distribution approach indicated that the estimated SEM particle domain size decreased from 8.30 nm to 6.05 nm with increasing NaOH concentration. Among the investigated conditions, 8 M NaOH produced nanosilica with the highest purity and the smallest estimated SEM particle domain size. These findings indicate that NaOH concentration plays an important role in controlling silica extraction and the resulting characteristics of amorphous nanosilica synthesized from local volcanic sand. The synthesized nanosilica may be further explored for applications requiring high surface area, such as adsorbents, catalyst supports, and functional composite fillers.